How to be an effective manager - Khaw, Steven; Dynamic Network System (M) Sdn. Bhd. ([S.l.] : Dynamic Network System (M) Sdn. Bhd., 2003)
Contains tips on how to be an effective manager, bonus material and 100 management tips
In Microsoft Word and Power Point format
Keywords: Personnel management; Supervision of employees; Industrial relation